Analyzing The Influence of Lecturer-Selected Audio on Students' Listening Comprehension - Nikijuluw, Renata C. G. V.; Aritonang, Parjolo (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2024)
One of the learning activities impacted by the transmission of the COVID-19 virus was a listening exercise in a university classroom. Regarding that assertion, listening comprehension requires help from learners' English language components and lecturers' aid. The study's objectives were: 1) to describe the influence of synchronous and asynchronous audio in online learning (Synchronous and Asynchronous in English Education Study Program); 2) to describe students' listening comprehension; and 3) to determine the positive and significant influence of synchronous and asynchronous audio in online learning on student listening comprehension. This study used a quantitative technique using Ex-post Facto research as the design. Purposive sampling was used to choose 32 students from the English Education Study Program in 2018 and 2019. A questionnaire was used to collect data, and the students' listening final grades were evaluated using IBM SPSS 20.0. The findings of this study revealed that: 1) Synchronous and Asynchronous at English Education Study Program was in the medium category, as the highest score was 76; 2) Students' Listening Comprehension was in the